2017
DOI: 10.5194/tc-2017-169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Network Model for Characterizing Brine Channels in Sea Ice

Abstract: Abstract. The brine network in sea ice is a complex labyrinth whose precise microstructure is critical in governing the movement of brine and gas between the ocean and the sea ice surface. Recent advances in three-dimensional imaging using x-ray micro-computed tomography have enabled the visualization and quantification of the brine network morphology and variability. Using imaging of first-year sea ice samples at in-situ temperatures, we create a new mathematical network model to characterize the topology and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…X-ray tomography studies of frozen sea ice show vertical liquid channels extending to depths of several millimeters. 38,40 Conversely, a different X-ray tomography study showed that cesium chloride in frozen aqueous solutions was concentrated in distinct unconnected pockets rather than in channels. 39 Our results are consistent with both studies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…X-ray tomography studies of frozen sea ice show vertical liquid channels extending to depths of several millimeters. 38,40 Conversely, a different X-ray tomography study showed that cesium chloride in frozen aqueous solutions was concentrated in distinct unconnected pockets rather than in channels. 39 Our results are consistent with both studies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The smallest pores, referred to as brine-layers have sizes in the sub-millimetre range and a spacing of around 1 mm [24]. A brine layer may disappear, join another brine layer or split into many layers upon ice growth [37,38]. A mathematical model developed by Lieblappen et al [38] supported by X-ray micro-computed tomography imaging of sea-ice, have demonstrated that brine layers with size between 100 and 200 μm have a higher probability to remain during seaice growth.…”
Section: Discussionmentioning
confidence: 99%
“…A brine layer may disappear, join another brine layer or split into many layers upon ice growth [37,38]. A mathematical model developed by Lieblappen et al [38] supported by X-ray micro-computed tomography imaging of sea-ice, have demonstrated that brine layers with size between 100 and 200 μm have a higher probability to remain during seaice growth. A brine channel of 100 μm in size that can generate tensile stress of 3.7 MPa (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation